ANALISIS RESPON MAHASISWA TERHADAP MEDIA PEMBELAJARAN BERBASIS EDMODO PADA MATA KULIAH PEMROGRAMAN KOMPUTER - Nurina Hidayah; Sayyidatul Karimah; Rini Utami (Universitas Pekalongan, 2018)
Analysis of student responses in this study aims to determine the quality of Edmodo-based learning media products that have been developed. The results obtained on average show 81% of this indicates a positive response from students. The most prominent of the six indicators used are happy and interesting. The statement of happy indicator that is learning with learning media based on Edmodo make student happy to reach 88%. While the interesting indicator states Edmodo-based learning media is new in the lecture.